Determinan Pertumbuhan Laba Pada Perusahaan Otomotif di Bursa Efek Indonesia - Hidayat, Akmal (Lembaga Riset Ilmiah, 2022)
This study aims to determine the determinants of profit growth in automotive companies on the Indonesia Stock Exchange. Factors studied include Total Assets Turnover Ratio, Debt To Total Assets, and Quick Ratio. This research is included in the quantitative research. The population of this study is 10 automotive companies listed on the Indonesia Stock Exchange (IDX. By using purposive sampling. This data is in the form of annual financial statements of automotive companies that have been audited and published. The analysis technique used in this study is multiple linear regression. Based on the results Data analysis shows that Total Assets Turnover and Quick Ratio partially have a significant effect on Profit Growth, while Debt To Total Assets has no significant effect on Profit Growth. Total Assets Turnover, Debt To Total Assets, and Quick Ratio simultaneously have an effect on Profit Growth.